WATER-RESOURCE POTENTIAL OF KHARKIV REGION: PROBLEMS OF USE - Клименко, Валентина; Решетченко, Світлана; Машкіна, Вікторія (Human Geography Journal, 2016)
In the article the main attention is given to water-resource potential of Kharkov region - surface waters. The main water bodies of the region are rivers and ponds. Local runoff, which is used for domestic drinking needs, energy, irrigation, industry and agriculture, is characterized in the article. The dynamics of water intake is analyzed, the key trends, problems of the water resources usage of Kharkov region and its districts and ways of their savings are identified.